The Effect Of Employee Commitment And Organizational Climate On Employee Motivation At The Service Of Population And Civil Registration In Pinrang District - Mustamin B (CV Putra Publisher, 2023)
The study aims to explore the effect of employee commitment and organizational climate on employee motivation at the service of population and civil registration in pinrang district by using quantitative approach. The author conducted research at the Department of Population and Civil Registry of Pinrang Regency, located in Pinrang Regency. In this study, the population was employees at the Office of Population and Civil Registry of Pinrang Regency, Pinrang Regency, totaling 39 people. Data collection techniques were carried out through distributing questionnaires and interviewing respondents, as well as other data that supports the subject matter of this discussion. In addition, data is obtained through information and documents, as well as literature related to the problem under study. To answer the main problems raised, the analytical method used is descriptive analysis and multiple linear regression. The data was analyzed by using SPSS 16.0 for Windows software. The result shows that the variables of Employee Commitment and Organizational Climate together have a significant effect on employee motivation at the Department of Population and Civil Registry of Pinrang Regency.